THE PROCESS OF IMPROVEMENT OF FOLK INSTRUMENTS IN UZBEKISTAN AND THE ORGANIZATION OF MULTIPLE ORCHESTRA AND ENSEMBLES - Tursunov Zohidjon Abduraimovich (Journal Park Publishing, 2024)
This article is devoted to the modernization of folk instruments in Uzbekistan and the formation of polyphonic orchestras and ensembles. Annotation: This article is about modernization of folk instruments in Uzbekistan and the formation of polyphonic orchestras and ensembles. the establishment of a family of instruments in the creation of orchestras and ensembles, as well as the shortcomings in this direction.
Keywords: National instruments, modernization, diatonic, chromatic, range, orchestra, ensemble, temperature, register, tanbur, chang, kashgar rubob, afghan rubob, gijjak, dutar.